IMPLEMENTASI BERAGAM METODE LAYANAN BIMBINGAN DAN KONSELING DI SMP N 37 SEMARANG: STUDI KASUS PPL 1 - Ardhi Ginanjar Prabowo, Tri; Sari Setianingsih, Eka; Yusmiati, Rini (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to investigate the application of various guidance and counseling service methods at SMP N 37 Semarang, focusing on classical guidance, group guidance and individual counseling. A case study approach was taken in the research, where the researcher carried out field practice during the PPL 1 period at the junior high school. The research results show that using the Problem Based Learning (PBL) method in classical guidance increases students' understanding of time management. Meanwhile, applying the Contextual Teaching and Learning (CTL) method in group guidance provides a deeper perspective on sensitive issues such as grooming children. On the other hand, group counseling using Brainstorming techniques and individual counseling using a Behavioral approach help students overcome various social and academic challenges. These findings provide a more comprehensive understanding of the effectiveness of various guidance and counseling service methods at the junior high school level, and contribute to the development of guidance and counseling practices in Indonesia.